Analisis Proses Pembentukan Tujuan Pembelajaran Berdasarkan Capaian Pembelajaran di SDN Sukasari 4 Kota Tangerang - Magdalena, Ina; Rahman, Rif’an Maulana (ANWARUL, 2023)
Teacher competence is seen from active performance and innovation that is continuously updated according to the characteristics of students every year. The Learning Implementation Plan (RPP) needs to be prepared properly and in detail to support teaching and learning activities that are seen based on existing potentials. This research is a type of qualitative research to determine the process of forming learning objectives based on learning outcomes at SD Negeri 4 Tangerang City. The author uses data collection techniques in the form of problem observations at SDN 4 Tangerang City, and interviews with grade 3 teachers at SDN 4 Tangerang City. The results of this study show that indicators in determining learning objectives consist of 2 aspects, namely conformity with indicators of competency achievement, and the formulation of learning objectives includes the completeness of the material.